Synthesis of highly calibrated CsPbBr3 nanocrystal perovskites by soft chemistry. Issue 40 (27th April 2022) - Mayer, Cédric R.; Levy-Falk, Hugo; Rémond, Maxime; Trippé-Allard, Gaëlle; Fossard, Frédéric; Vallet, Maxime; Lepeltier, Marc; Guiblin, Nicolas; Lauret, Jean-Sébastien; Garrot, Damien; Deleporte, Emmanuelle
Abstract : Highly calibrated CsPbBr3 NC perovskites by soft chemistry, highlighting the role of phenylethylamine acting like a pair of scissors to cut bigger NCs. Abstract : A new synthetic method for preparing highly calibrated CsPbBr3 nanocrystal perovskites is described and analyzed using high-resolution scanning transmission electron microscopy. This new method based on soft chemistry leads to the large-scale production of nanocrystals. Such monodisperse nanocrystals allow for the deposition of homogeneous films, which provides new opportunities for the next generation of optoelectronic devices.